The Effect of Harness Training on Increasing 400 M Short Distance Running Speed of PASI Athletes - Widiyanto, Erik; Junaidi, Ilham Arvan; Lanos, Muhsana El Cintami (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This study aimed to assess the effect of harness training on the speed of 400-meter short-distance running among athletes from PASI in Bandar Lampung. Utilizing a quasi-experimental design, the research involved a sample of 6 athletes. The data analysis comprised conducting prerequisite tests and performing t-tests to evaluate the impact. The findings demonstrated a significant improvement in running speed due to harness training, with a calculated t-value of 8.164, which is notably higher than the tabulated t-value of 1.81. This substantial difference indicates a statistically significant effect. Therefore, it can be concluded that harness training has a considerable and positive influence on enhancing the 400-meter running speed of PASI athletes in Bandar Lampung.